PHYSICO-CHEMICAL CHARACTERISTICS OF YELLOW VARIETY OF SEABUCKTHORN (HIPPOPHAE RHAMNOIDES L) - Zeb, A.; Khan, Z. A.; Qazi, I. M.; Ullah, Ihsan (The Nucleus, 2020)
This study was carried out to evaluate the physico-chemical composition of seabuckthorn yellow variety wildly grown in northern areas of Pakistan. The sites selected were Skardu, Shigar, Khaplu and Hunza. The analysis of the fruit was carried out in the form of whole berries, pulp and seed. The parameters studied were pH, acidity, sugar, protein, ascorbic acid, moisture, total soluble solids (TSS), ash and oil. Mean moisture contents had the figures of 68.68, 72.18 and 20.39% in whole berries, pulp and seed, respectively. The ash levels from four sites were found in the range of 2.13-2.64 (whole), 0.79-1.01 (pulp) and 1.05-1.28% (seed). Maximum mean concentrations of various parameters determined were 11.06 (TSS), 14.73 (crude oil), 24.86 (crude protein), 1.58% (titratable acidity) and 53.58 mg/100g (ascorbic acid). Highest contents in the pulp for total and reducing sugars were 8.33 and 7.39% while maximum non-reducing level was observed in whole berries (1.43%). Mean total soluble solids (TSS) determined was 9.56 (whole) and 11.06 obrix (pulp).